1984
DOI: 10.1016/s0735-1097(84)80178-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fluctuations in blood and spleen radioactivity: Splenic contraction and relation to clinical radionuclide volume calculations

Abstract: Alterations in the blood radioactivity affect ventricular volume calculations using count-based radionuclide ventriculography. To study this phenomenon, the effect of time, posture and supine exercise on blood radioactivity, red blood cell count and splenic radioactivity was evaluated. The red blood cell count, and blood, splanchnic and splenic radioactivity remained stable in five patients studied at rest in the supine position. On standing, blood radioactivity increased 10 +/- 3% (standard error of the mean)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 21 publications
3
37
1
Order By: Relevance
“…Physical exercise has been found to be associated with increased production of PGI 2 in humans 25–27 . Interventions stimulating sympathetic nerve activity have been demonstrated to induce contraction of the spleen, with a subsequent increase in haematocrit and haemoglobin concentrations in the peripheral blood in humans, 28–33 although these findings are in contrast with the view of earlier studies showing no reservoir function for blood cells in the human spleen 34,35 . The present findings in dogs cannot be extrapolated simply to the clinical situation, but suggest that PGI 2 may play a role to relieve exercise‐induced splenic contraction, in addition to the adrenergic neurotransmission, and thereby reduce blood cell concentrations and blood viscosity.…”
Section: Discussioncontrasting
confidence: 70%
“…Physical exercise has been found to be associated with increased production of PGI 2 in humans 25–27 . Interventions stimulating sympathetic nerve activity have been demonstrated to induce contraction of the spleen, with a subsequent increase in haematocrit and haemoglobin concentrations in the peripheral blood in humans, 28–33 although these findings are in contrast with the view of earlier studies showing no reservoir function for blood cells in the human spleen 34,35 . The present findings in dogs cannot be extrapolated simply to the clinical situation, but suggest that PGI 2 may play a role to relieve exercise‐induced splenic contraction, in addition to the adrenergic neurotransmission, and thereby reduce blood cell concentrations and blood viscosity.…”
Section: Discussioncontrasting
confidence: 70%
“…prolonging apnea duration [4]. Splenic contribution of Hb to the circulating blood volume has also been observed in healthy subjects during exercise [10][11][12] and more recently during altitude simulation by normobaric hypoxia [13,14]. This suggests that spleen contraction may be an emergency response triggered in a number of circumstances involving hypoxia.…”
Section: Introductionmentioning
confidence: 89%
“…Although a few smallscale early studies based on changes in haemoglobin and haematocrit found no change in volumes of the human spleen with exercise (Dill, Talbott, & Edwards, 1930;Ebert & Stead, 1941), at least nine more recent studies of maximal effort (Agostoni et al, 1999;Allsop et al, 1992;Flamm et al, 1990;Froelich, Strauss, Moore, & McKusick, 1988;Laub et al, 1993;Lodin-Sundström, Schagatay, Schagatay, & Engan, 2014;Otto, Rona du Toit, Pretorius, Lötter, & van Aswegen, 1995;Sandler et al, 1984), mostly using the more precise technologies of technetium scintigraphy or ultrasound, found splenic contractions of 11-66% (average 42%), with a corresponding increase in circulating red blood cell volumes. Decreases of splenic volume have also been observed with various forms of apnoea (Baković et al, 2005;Baković, Valic, Eterović, Vukovic, Obad et al, 2003;Espersen, Frandsen, Lorentzen, Kanstrup, & Christensen, 2002;Hurford et al, 1990;Inoue, Nakajima, Mizukami, & Hata, 2013;Lodin-Sundström & Schagatay, 2010;Palada et al, 2007;Prommer et al, 2007;Richardson et al, 2005;Schagatay, Andersson, Hallen, & PĂ„lsson, 2001;Schagatay, Haughey, & Reimers, 2005) (Table I), hypoxia (Lodin-Sundström & Schagatay, 2010;Richardson, Lodin, Reimers, & Schagatay, 2008), infusion of adrenaline (Baković, Pivac, Zubin Maslov, Breskovic, & Damonja et al, 2013;Knecht, Jost, GmĂŒr, Burger, & Fehr, 1988), drowning (probably a response to a combination of hypoxia and cooling) (Haffner, Graw, & Erdelkamp, 1994) and splenic nerve stimulation (a very much smaller response than seen in horses) (Ayers et al, 1972), with changes in total red cell volume abolished by splene...…”
Section: Response Of Spleen To Stressmentioning
confidence: 99%